A Novel Hybrid Type (Custom-Made plus off-the-Shelf) Total Femoral PROSTALAC. Issue 4 (25th July 2016) - Araç, Süleyman Şükrü; Boya, Hakan
Introduction: Treatment of periprosthetic joint infection following revision-Total Hip Arthroplasty is more problematic when there is poor bone quality and severe bone loss. Migration of revision prosthesis with a long stem to the knee joint in infected cases makes treatment more complex. In these cases, total femoral replacement is the only treatment option and eradication of infection is mandatory before the replacement. In 2-staged reconstruction treatment, there is a need for a PROSTALAC to replace the whole femur. Methods: We describe here a novel hybrid type (custom-made plus off-the-shelf) total femoral PROSTALAC for cases in need of whole femoral bone and femoral component removal for the treatment of periprosthetic joint infection in total hip arthroplasty. Result: Both sides of the PROSTALAC have anatomical joint surfaces, so the articulation with the acetabulum proximally is expected to be more stable. The off-the-shelf anatomic joint surface of the PROSTALAC distally allows articulation compatible with a proximal tibial off-the-shelf spacer. Conclusions: This simple hybrid-type total femoral PROSTALAC can be adjusted to femoral length, has anatomical joint surfaces that produce a more stable articulation, and can articulate with an off-the-shelf proximal tibial spacer.